Catalytic etherification of glycerol to tert-butyl glycerol ethers using tert-butanol over sulfonic acid functionalized mesoporous polymer. Issue 86 (5th September 2016) - Manjunathan, Pandian; Kumar, Manish; Churipard, Sathyapal R.; Sivasankaran, S.; Shanbhag, Ganapati V.; Maradur, Sanjeev P.
Abstract : Mesoporous polymers (MP) were synthesized by free radical polymerization of divinylbenzene by a solvothermal method followed by sulfonic acid functionalization by a post synthetic modification with conc. Abstract : Mesoporous polymers (MP) were synthesized by free radical polymerization of divinylbenzene by a solvothermal method followed by sulfonic acid functionalization by a post synthetic modification with conc. H2 SO4 . MP-SO3 H was characterized by various physicochemical techniques such as FT-IR, nitrogen sorption, CHNS analysis, acid–base titration and TGA. MP-SO3 H was demonstrated to be a highly active heterogeneous acid catalyst, providing a high yielding route for the synthesis of h-GTBE through the etherification of bio-renewable glycerol with tert -butanol. MP-SO3 H containing optimum acidity and a large mesoporous surface area gave 44% h-GTBE selectivity at 86% glycerol conversion under optimized reaction conditions. The catalytic performance of MP-SO3 H was found to be superior over other conventional porous solid acid catalysts.